Mapping: Farming from the ground up - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2010)
Agricultural researchers throughout Africa are using the latest technology to develop a digital map showing the properties of soil across the continent. Farmers will be able to get detailed information on soil fertility in their area.